Reflexões sobre a customização em massa no processo de provisão de habitações de interesse social : estudo de caso na COHAB de Londrina-PR - Taube, jaqueline (2015)
Researches show that the social housing which are developed in Brazil have not been meeting the real needs of final customers. This raises adaptation needs made by users in the built environment which results in low quality housing. An alternative to increase the product´s value is to use the mass customization strategy in the pre-made houses production. The mass customization can be defined as a strategy that allows final customers a range of product options, based on their needs, with costs and delivery time similar to that in mass production which will reach a higher number of satisfied customers. This dissertation aims to identify the obstacles and opportunities to social housing mass customizing focused on families with an income up to R$1.600,00. This research development began with literature review for a clear comprehension of the mass customization concept and its implications in the house building context. The adopted research strategy is the case study made in the Housing Company in Londrina - PR. The research method was split in two phases: the customers demands characterization, accomplished by data analysis of a Post-occupancy Evaluation made in an enterprise with similar features to the case study, and the case study made in Housing Company in Londrina, aiming to identify the possibility of implementing customers involvement points in the social housing provision process. In conclusion, this project presents the flow mapping organizational of the provision process the social housing in housing company in Londrina and the customers requirements for this type of housing. With this dissertation´s development permitted to identify that the mass customization is possible in this context. It was found that the social housing provision presents various opportunities, but also obstacles for the mass customization implementation in this context. It was also possible to check customers needs and to consider this information during the housing unit development process. This study also shows that the two product development processes, including the housing production e the family´s selection must be developed simultaneously. Finally, it is recommended the use of a building system which allows speed and flexibility, so that the customer´s order penetration point, or the family´s definitions, may be close to the units final phase